Developing and Validating Clinical Questionnaires - Rosellini, Anthony J; Brown, Timothy A (Annual review of clinical psychology, 2021)
Coinciding with the development and revision of conceptual models of psychopathology, there has been a proliferation in the number of self-report clinical questionnaires and studies evaluating their psychometric properties. Unfortunately, many clinical measures are constructed and evaluated using suboptimal methods. This review provides current guidelines for the conceptualization, development, and psychometric validation of clinical questionnaires using latent variable methods. A two-stage exploratory-confirmatory framework is provided. The exploratory stage includes item selection and revision, initial structural evaluation, and preliminary tests of concurrent validity (e.g., convergent and discriminant). The confirmatory stage involves replicating factor structure using a more restrictive model, identifying areas of model strain, conducting additional tests of concurrent and predictive validity, and evaluating measurement invariance. Recommendations are provided for ( ) item generation, ( ) how to use different types of exploratory and confirmatory factor models to determine structure, and ( ) evaluating reliability and validity using a latent variable measurement model approach.